The relationship of glenoid version and severity of glenoid bone loss in anterior shoulder instability patients: A retrospective cohort study - Nattakorn Paopongthong; Pichitchai Atthakomol; Chanakarn Phornphutkul (Elsevier, 2022)
Background/objective: The effect of glenoid version on the severity of glenoid bone loss is not completely understood, although the variation of glenoid version angles is considered to reflect the degree of glenoid bone loss in anterior shoulder instability cases. The objective of this retrospective case-control study is to determine the relationship of the glenoid version and the severity of glenoid bone loss in a group of previously documented recurrent anterior shoulder dislocation patients. Methods: We retrospectively collected magnetic resonance arthrogram (MRA) data from 72 patients with unidirectional recurrent anterior shoulder instability. The best-fit circle method was used to identify the percentage of glenoid bone loss. Measurements of glenoid labral, chondral, and bony versions were performed using the Friedman method. Results: Using univariate regression analysis, it was found that a retroversion angle of more than 4 degrees was associated with an increased risk ratio for the occurrence of a critical glenoid defect by approximately 5 times. Conclusions: 24 Univariate logistic regression analysis, used to determine the presence of a critical glenoid bone defect, showed that both the bony version angle and the number of previous dislocations were significantly associated with the extent of glenoid bone loss. A retroversion angle of more than 4 degrees was associated with an approximately five-fold increase in the odds ratio for the presence of a critical glenoid defect. Surgeons may use the value of the measured glenoid version in prediction the required version of the reconstructive treatment.